PERBANDINGAN PEMBELAJARAN SAINTIFIK MENGGUNAKAN MODEL KOOPERATIF TIPE STUDENT FASILITATOR AND EXPLAINING (SFE) DAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR KIMIA - Florentina Astiani; Amrul Bahar; Hermansyah Amir (University of Bengkulu, 2019)
This study aims to determine differences in student learning outcomes in chemistry learning using cooperative learning model of Student Facilitator and Explaining (SFE) type and Student Teams Achievement Division (STAD) on the subject of compound nomenclature. This research type is quasi experiment research with population that is class X MIPA in SMAN 9 Kota Bengkulu even semester of academic year 2017/2018 while sample is class X MIPA 2 and class X MIPA 4 obtained from result of normality test and homogeneity test. Student learning outcomes in this study is seen from the difference between pretest and posttest values. Data analysis used were mean value, normality test, homogeneity test and hypothesis test (t test). The average of pretest and posttest difference of the students in the experimental class I (SFE) was obtained 58.70 while in the experimental class II (STAD) obtained the value 54.25. So it can be concluded that student learning outcomes that apply SFE type cooperative model is higher than student learning outcomes that apply STAD type. After testing hypothesis with significant level (? = 0,05), then obtained tcount value> ttable that is 1.782819 > 1.67469. The results showed that there was a significant difference between experimental class I using SFE type cooperative learning model and experiment II class using STAD type.